2020
DOI: 10.3390/ijms21061968
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP2 Inhibits Migration and Invasion of Gastric Cancer Cells via Elevating SHIP2 Phosphatase Activity

Abstract: Previous studies have shown reduced expression of Src homology 2-containing inositol 5-phosphatase 2 (SHIP2) and its tumor-suppressive role in gastric cancer (GC). However, the precise role of SHIP2 in the migration and invasion of GC cells remains unclear. Here, an IQ motif containing the GTPase-activating protein 2 (IQGAP2) as a SHIP2 binding partner, was screened and identified by co-immunoprecipitation and mass spectrometry studies. While IQGAP2 ubiquitously expressed in GC cells, IQGAP2 and SHIP2 co-local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Furthermore, we identified IQGAP2 as a downstream target of miR-10b-5p in TNBC cells. Recently, IQGAP2 has been reported as a tumor suppressor in many cancers including prostate cancer [33] , gastric cancer [34] and ovarian cancer [35] . Consistently, our findings showed that IQGAP2 was lowly expressed in TNBC cells and upregulated expression of IQGAP2 suppressed the malignant behaviors of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified IQGAP2 as a downstream target of miR-10b-5p in TNBC cells. Recently, IQGAP2 has been reported as a tumor suppressor in many cancers including prostate cancer [33] , gastric cancer [34] and ovarian cancer [35] . Consistently, our findings showed that IQGAP2 was lowly expressed in TNBC cells and upregulated expression of IQGAP2 suppressed the malignant behaviors of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IQGAP1, the IQGAP protein family includes IQGAP2 and IQGAP3, which are both structurally similar to IQGAP1, but are expressed in more limited types of organs [1,12]. The roles of these two proteins, particularly IQGAP3, in carcinogenesis, are less well understood, but the emerging picture is that, while IQGAP3 functions similarly to IQGAP1 as an oncogene, IQGAP2 may serve as a tumor suppressor [12,[81][82][83][84][85]. Further studies into how IQGAP2 and IQGAP3 contribute to cancer and how the IQGAP proteins compensate or coordinate with each other will shed more light on IQGAP-mediated carcinogenesis and related therapy designs.…”
Section: Iqgap1 Plays An Essential Role In Many Types Of Cancermentioning
confidence: 99%
“…With respect to IQ motif-containing GTPase-activating protein 2 (IQGAP2), it functions as a scaffolding protein that regulates the cytoskeleton by juxtaposing Rho GTPase and Ca 2+ /calmodulin signals 26 . Low expression of IQGAP2 has been identified in ovarian cancer, prostate cancer, hepatocellular carcinoma and gastric cancer [27][28][29][30] , suggesting that IQGAP2 functions as a tumor suppressor. However, the IQGAP2 biological functions in DR are yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%